2009
DOI: 10.1364/oe.17.007893
|View full text |Cite
|
Sign up to set email alerts
|

Low-threshold two-photon pumped ZnO nanowire lasers

Abstract: We report in this communication the two-photon absorption (TPA)-induced room-temperature lasing performance of ZnO nanowires. Under femtosecond pulse-excitation at lambda = 700 nm in the infrared regime, a remarkably low threshold of 160 microJ/cm(2) was observed for the TPA-induced lasing action, which is of the same order of magnitude as that measured for the linear lasing process. Time-resolved photoluminescence characterization of two-photon pumped ZnO nanowires reveals the presence of a fast decay (3-4 ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
65
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(65 citation statements)
references
References 28 publications
0
65
0
Order By: Relevance
“…Stimulated emission due to two-and three-photon absorption with a high threshold of 100 mJ/cm 2 was also reported in ZnO nanowires [123]. Zhang et al further studied this and demonstrated a lower threshold of 160 µJ/cm 2 from two-photon absorption of ZnO nanowires pumped with a pulsed laser at 700 nm [125]. Following these pioneering works, II-VI compounds became the focus of investigation, and Lieber's group at Harvard University first studied the lasing properties of CdS nanowires and the effect of temperature on the lasing threshold [24].…”
Section: (A) Materialsmentioning
confidence: 73%
“…Stimulated emission due to two-and three-photon absorption with a high threshold of 100 mJ/cm 2 was also reported in ZnO nanowires [123]. Zhang et al further studied this and demonstrated a lower threshold of 160 µJ/cm 2 from two-photon absorption of ZnO nanowires pumped with a pulsed laser at 700 nm [125]. Following these pioneering works, II-VI compounds became the focus of investigation, and Lieber's group at Harvard University first studied the lasing properties of CdS nanowires and the effect of temperature on the lasing threshold [24].…”
Section: (A) Materialsmentioning
confidence: 73%
“…These emissions make ZnO, a very interesting material for various optoelectronic applications. ZnO is now being used as UV absorbing material in sunscreens (Schilling et al 2010), transparent conductors in solar cells (Lloyd et al 2009), and nano-lasers (Zhang et al 2009). Recently Wang (2008) has successfully demonstrated energy generation from arrayed ZnO nanorods using the piezo-electric property exhibited by this material.…”
Section: Introductionmentioning
confidence: 99%
“…in nano-lasers) to be implemented in novel photonic circuits. A lack of inversion symmetry inherent to wurtzite crystal lattice of ZnO facilitates strong nonlinear optical effects in this material such as second-harmonic generation [7][8][9][10] and twophoton-absorption (TPA) [11][12][13][14][15]. The latter process often leads [10] to PL upconversion, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…appearance of efficient near-band-edge (NBE) photoluminescence (PL) arising from recombination of non-equilibrium carriers generated due to energy upconversion via TPA under optical excitation with photon energy below the bandgap energy. Therefore, TPA is currently considered [15] as an attractive practical approach for exciting the PL emission in ZnO as it allows us to replace expensive UV pumping sources in photonic circuits by inexpensive near-infrared-laser diodes based on III-V semiconductors.…”
Section: Introductionmentioning
confidence: 99%